Stress and eating behaviours in healthy adults: a systematic review and meta-analysis. Issue 2 (3rd April 2022) - Hill, Deborah; Conner, Mark; Clancy, Faye; Moss, Rachael; Wilding, Sarah; Bristow, Matt; O'Connor, Daryl B.
ABSTRACT: Stress leads to detrimental health outcomes through direct biological and indirect behavioural changes. Stress can lead to disruption to normal eating behaviours, although the strength of these associations is unknown. This is the first meta-analysis to determine the strength of the stress-eating relationship in healthy adults and to explore the impact of potential moderators. Studies included had a clearly defined measure of stress (i.e., any noxious event or episode in one's environment with the exclusion of emotional distress) that was linked to non-disordered eating. Key terms were searched in Medline, PsycInfo and Ovid databases (23, 104 studies identified). 54 studies (combined N  = 119, 820) were retained in the meta-analysis. A small, positive effect size was found for the stress-overall food intake relationship ( Hedges' g =  0.114). Stress was associated with increased consumption of unhealthy foods ( Hedges' g =  0.116) but decreased consumption of healthy foods ( Hedges' g =  −0.111). Only one significant moderator (restraint on stress-unhealthy eating) was identified. This meta-analysis identified the magnitude of the effect of stress on eating behaviour outcomes. Significant heterogeneity was observed that was not explained by the moderators examined. Further research on moderators of the stress-eating relationship is required and should distinguish effects for healthy versus unhealthy eating.